Metallothionein (MT) Expression and SEM-EDX Mapping on Cymodocea serrulata Seagrass - Dwi Rosalina; Dini Sofarini; Firman Farid Muhsoni; Misbakhul Munir; Ruly Isfatul Khasanah (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight Research 1. Metallothionein is a protein found in seagrass and functions to bind to heavy metals so as not to damage the seagrass body tissue Abstract Lead is a very dangerous heavy metal for organisms because it is carcinogenic, can cause mutations, takes a long time to decompose and has unchanging toxicity. This study on the seagrass Cymodocea serrulata aimed to determine the metallothionein expression quantitatively using the Elisa (Enzyme-Linked Immunosorbent Assay) method and describe the surface structure of C. serrulata roots, rhizomes, and leaves that were exposed to lead using SEM and EDX Mapping methods. The results showed that metallothionein was abundant in C. serrulata tissues (leaves>roots>rhizomes) in both South Bangka and Ketawai Island. SEM showed changes in the morphology and cell size of C. serrulata exposed to lead. EDX and Mapping showed the substance elements found in seagrass tissue. Pb was detected in C. serrulata roots (0.22%) and leaves (0.6%) in South Bangka. This indicates that the seagrass plants are able to absorb heavy metals into their body tissues.